La familia Aulacidae en Chile (Hymenoptera: Evanioidea) - Elgueta, M.=700 1 Lanfranco, D.
(Es, En)
Ilus., 24 ref.
Keywords: HYMENOPTERA; EVANIIDAE; ESPECIES NUEVAS; IDENTIFICACION; CHILE; PRISTAULACUS; AULACUS; REVISTA CHILENA DE ENTOMOLOGIA